Kinematic analysis of the effect of altered transtibial prosthetic static load line on asymmetry - Jutima Rattanakoch (2018)
© 2016 IEEE. To date, there are no studies having assessed the relative outcomes of the final dynamic prosthetic alignment and the recommended static alignment, and how these are related. Does the recommended static alignment produce more symmetrical gait during dynamic analysis in terms of kinematic measurement? This project aimed to evaluate the clinical results of the final total static load line using a three dimensional motion analysis system by measuring the differences between the final total static load line and the recommended static alignment, and then to compare the effect of total static load line changed with asymmetrical individual gait pattern in terms of kinematic analysis. Ten unilateral transtibial amputees with at least one year experience of endoskeletal transtibial prosthesis user participated in this study. All participants routinely used the same prosthetic type endoskeletal prosthesis with patellar tendon bearing socket and multi-Axial prosthetic foot. The Vicon® motion capture system was used to collect the static and dynamic data and the differences in gait parameters values between two groups of participants with their static load lines anteriorly or posteriorly to the knee joint center was analyzed. To compare both sides of the symmetrical gait data within subjects, a general linear model for repeated measures was applied. The kinematic variables showed that the joint relative angles were of more symmetrical in the posterior load line groups, while the anterior load line group presented more symmetrical in terms of time and distance parameters. Moreover, the kinematic parameters which compared between the prosthetic side and the sound side were not influenced by how severely the final prosthetic alignment differed from the recommended static alignment. Further investigations, preferably with an increased number of participants and more direct comparisons with previous studies' results through the use of the same measurement systems would allow for improved results.